Construcción del mundo de la vida del niño mapuche en un aula de Temuco: Construction of the Life World of the Mapuche Child in a Classroom in Temuco - Huaiquián Billeke, Claudia; Briceño Carillanca, Ximena; Huenullanca Neculpán, Cecilia; Poblete Jara, Karina (Universidad del Zulia, 2022)
The purpose of this manuscript is to reveal the construction of the world of life of Mapuche children in a school in Temuco. The interaction and coexistence of the Mapuche child with their peers in everyday life is investigated. The method is qualitative, it is situated from an ethnomethodological approach and a single case design. Semi-structured interviews and non-participant observation were applied. The analysis is carried out from a data reduction by the Atlas ti program through open and axial coding procedures. It is concluded that the experiences and customs of the child, as well as the construction and inclusion of Mapuche identity, in a classroom is constructed from non-Mapuche Western-type school education.